2014
DOI: 10.3389/fnagi.2014.00243
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term CDK5 knockdown prevents spatial memory dysfunction and tau pathology of triple transgenic Alzheimer’s mice

Abstract: CDK5 is a member of the cyclin-dependent kinase family with diverse functions in both the developing and mature nervous system. The inappropriate activation of CDK5 due to the proteolytic release of the activator fragment p25 from the membrane contributes to the formation of neurofibrillary tangles and chronic neurodegeneration. At 18 months of age 3xTg-AD mice were sacrificed after 1 year (long term) or 3 weeks (short term) of CDK5 knockdown. In long-term animals CDK5 knockdown prevented insoluble Tau formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 52 publications
(69 reference statements)
1
38
0
2
Order By: Relevance
“…Such vectors exhibit conserved silencing efficiency and effects on specific substrates, as we have verified in an Alzheimer's disease mouse model. 31 Several studies have described the administration of siRNA against pathogenic genes involved in cerebral ischemia-induced apoptotic cell death and inflammation. 32 However, it is important to emphasize that in such studies, the siRNA was delivered before the ischemic event, restricting the translation of such a protocol into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Such vectors exhibit conserved silencing efficiency and effects on specific substrates, as we have verified in an Alzheimer's disease mouse model. 31 Several studies have described the administration of siRNA against pathogenic genes involved in cerebral ischemia-induced apoptotic cell death and inflammation. 32 However, it is important to emphasize that in such studies, the siRNA was delivered before the ischemic event, restricting the translation of such a protocol into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Among these kinases, Cdk5 is particularly interesting because it may play a crucial role in the pathogenesis of AD and regulate activity of other critical kinases including Gsk-3β. An increasing number of studies in vitro and in vivo have shown that Cdk5 has a strong relationship with the phosphorylation of tau and the progression of neurofibrillary tangles [62,63]. Cdk5 mediated-hyperphosphorylation of tau makes tau no longer connect with the microtubules but aggregates into the filaments and tangles, ultimately leading to synaptic loss and neuronal death.…”
Section: Cdk5 Mediates Tau Hyperphosphorylationmentioning
confidence: 99%
“…Studies from our group have demonstrated that CDK5 silencing with RNA interference reduces pathological markers, such as NFTs, and improves cognitive function in triple-transgenic AD mice (Castro-Alvarez et al, 2014a;Piedrahita et al, 2010). However, the possible roles of the CDK5 protein and p35, the specific activator of CDK5 in astrocytes, are associated with regulation of the microtubule cytoskeleton and formation of the glial scar after scratch wounds (He et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Under pathological conditions, the microtubule-associated protein tau (a substrate of CDK5) is hyperphosphorylated by CDK5 and other kinases, which induces the formation of toxic intracellular aggregates in both neurons and astrocytes. These aggregates are known as neurofibrillary tangles (NFTs), and are considered a pathological marker in AD and other tauopathies (Castro-Alvarez et al, 2014a, 2014bGarcía-Matas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%